A systematic review of the use of WeChat in teaching Chinese as a foreign language - Liu Weiming (Journal of China Computer-Assisted Language Learning)
Over the years, social media have gained popularity as tools for language teaching. The social media platform WeChat has been employed for teaching Chinese as a foreign language (TCFL). While studies have investigated the use of WeChat for TCFL, no systematic reviews have been conducted to provide an overview of existing research. This review article examines empirical studies on WeChat in TCFL, summarising their main characteristics, findings, and critically assessing the quality and relevance of the available evidence. Scopus and Web of Science were used as primary databases for this review. Relevant studies were identified by using keyword sets such as “WeChat Chinese language”, “WeChat Mandarin”, “WeChat Hanyu” and “WeChat Putonghua”. The review identified the contexts, research methods and themes of the selected articles. The main themes include language learning, social interactions, learner agency and motivation. The paper also discusses the implications of using WeChat for TCFL and highlights areas for future research. It is hoped that the insights provided here will inform the design and implementation of future courses that use WeChat or other technology-assisted applications for language teaching.